Classifying Students With School Refusal Behavior and Their Relationship to Learning Strategies - Giménez-Miralles, Mariola; Gonzálvez, Carolina; Sanmartín, Ricardo; Vicent, María; Aparicio-Flores, María del Pilar; García-Fernández, José Manuel (Frontiers in Education, 2021)
Students with School Refusal Behaviour (SRB) are a diverse group, often associated with negative academic repercussions (e.g., low academic performance, learning difficulties or academic demotivation). The aims of this research were: (1) to identify school refusal behaviour profiles based on low and high scores on the four functional conditions assessed by the School Refusal Assessment Scale-Revised (SRAS-R) and (2) to examine the relationship between SRB profiles and learning strategies. The SRAS-R and the Inventory of Learning and Study Strategies-High School version were administered to 1,261 students aged to 14 to 18 (M = 16.51; SD = 1.84). Four SRB profiles were obtained: SRB by positive reinforcement, Low SRB, SRB by negative reinforcement and Mixed SRB. School refusers belonging to the Mixed SRB and SRB by negative reinforcement profiles are characterised by low scores on learning strategies, except for the Anxiety dimension. The practical implications of these findings suggest that implementing study techniques and learning strategies programmes, in addition to courses on anxiety management and self-care will help students improve their learning paths and reduce anxiety-based school refusal.